2014
DOI: 10.1371/journal.pone.0116113
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Canopy Cover and Colony Size of the Wood Ant Formica lugubris - Implications for the Thermal Effects on a Keystone Ant Species

Abstract: Climate change may affect ecosystems and biodiversity through the impacts of rising temperature on species’ body size. In terms of physiology and genetics, the colony is the unit of selection for ants so colony size can be considered the body size of a colony. For polydomous ant species, a colony is spread across several nests. This study aims to clarify how climate change may influence an ecologically significant ant species group by investigating thermal effects on wood ant colony size. The strong link betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
2
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 56 publications
2
31
2
3
Order By: Relevance
“…Ants are subject to somewhat different constraints than most other ectotherms because they are eusocial. In terms of physiology, behaviour and genetics, the colony is the unit of selection for ants (Chen & Robinson, 2014) and thermal adaptation can thus occur via a variety of mechanisms. Here, we observed that the ant A. iberica displayed efficient behavioural thermal regulation at the colony level.…”
Section: Discussionmentioning
confidence: 99%
“…Ants are subject to somewhat different constraints than most other ectotherms because they are eusocial. In terms of physiology, behaviour and genetics, the colony is the unit of selection for ants (Chen & Robinson, 2014) and thermal adaptation can thus occur via a variety of mechanisms. Here, we observed that the ant A. iberica displayed efficient behavioural thermal regulation at the colony level.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, polydomy may result from constraints on nest size: as Temnothorax species live in small natural cavities such as hollow acorns or rotten twigs, a single nest may be too small to accommodate growing sexual brood in spring and early summer [20,21,[64][65][66][67]. Polydomy has also been suggested to act as a thermoregulatory mechanism [20,21,31,68,69], a bet-hedging strategy decreasing a colony's vulnerability to external risks [20,21,32,70], or a means for workers to escape queen control in intra-colonial reproductive conflicts [20,21,26,[71][72][73]. All these factors combined may contribute to trigger the foundation of polydomous nests in spring in Temnothorax species.…”
Section: Discussionmentioning
confidence: 99%
“…First, it is expected to reduce food search costs by increasing the total searched area while decreasing the overlap between foragers' search paths [5,6,[25][26][27][28][29][30]. Second, dispersed central-place foraging should decrease food transport costs by reducing the average distance between food sources and the nearest nest entrance [6,23,24,28,[31][32][33][34][35][36][37][38][39][40]. Third, foraging over a larger territory is considered beneficial by allowing colonies to diversify their food sources [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Nest attributes are those based directly on inherent attributes of the nest. The population of a nest (hereafter nest size), canopy cover over the nest, and the distance from the nest to the nearest tree all have been shown to be ecologically important for wood ants (Chen & Robinson, ) and therefore have the potential to influence the survival and reproduction of nests.…”
Section: Methodsmentioning
confidence: 99%